Fiscal planning and local government administration in Nigeria: The quest for sustainable rural development - Khalil, Samihah (Academic Journals, 2012)
The raison d’etre of a local government is to collect its revenue efficiently and to use that revenue to provide infrastructural development for its tax payers.Local government as the third tier of government cannot, therefore be ideal from the financial view lens if it collects its revenue in a slip-shod manner and devotes a large percentage of it to the maintenance of a top- heavy administrative set-up, with a relatively small proportion of the revenue left for the provision of infrastructural development which are of direct benefits to the local inhabitants.The purpose of this paper is to critically examine local government accountability in respect of budget and budgeting system in order to improve sustainable development at the local level.The paper tries to study the main source of revenue of local governments in Nigeria, and determine how the resources are utilized to deliver infrastructural development to the people.Also, information on budget and budgeting of Irepo local government is analyzed in the study.There are 774 local governments in Nigeria.This research study covers 33 local governments in terms of disbursement of statutory allocation, and Irepo local government in terms of budget and budgeting analysis. As far back as 1999, the Nigerian local governments are being given enough by the Federal Government in order to provide infrastructural development to the citizens in the local area, but it seems the said public revenue are being mismanaged by political leaders and local governments’ officials in Nigeria.The findings of this paper revealed that < 5% of the statutory allocation accrued to the local governments under consideration is being expended on infrastructural development, while > 10% is used for personnel expenditure as the cost of delivering infrastructural development by local governments in Nigeria.So, further researches can still be carried out on fiscal planning by local governments for sustainable development in the remaining local governments in Nigeria. This paper therefore recommended that the policy/decision-makers should make use of the findings of this study to help inform future decisions on fiscal planning in the local government administration in order to bring about sustainable development to the rural dwellers in the local governments.It is found that there is need for pro active measure for fiscal planning in order to sustain infrastructural development in the local government administration.Also found, is that local governments need to put in place a good fiscal planning that will sustain development at the local level.